RISK ASSESSMENT OF PROJECT MANAGEMENT OFFICE ACTIVITIES IN ENTERPRISES IN INSTABILITY CONDITIONS - BOZHANOVA, Olena; SHEPELENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines theoretical, methodological, and applied aspects of forming a regional strategy for improving service quality in the hotel and restaurant sector of Zakarpattia as a key factor in the sustainable development of the region’s tourism and recreational potential. The relevance of the study is driven by increasing competition in the tourism services market, growing consumer expectations regarding service quality, and the need for hospitality enterprises to adapt to contemporary socio-economic challenges and European integration processes.The study substantiates the role of service quality as a strategic resource for building competitive advantages of hotel and restaurant enterprises at the regional level. The specific features of the hotel and restaurant sector in Zakarpattia are analyzed, taking into account its border location, multicultural environment, seasonal tourist flows, and the predominance of small and medium-sized enterprises. Key service-related problems are identified, including workforce shortages, uneven quality standards, insufficient digitalization, and limited investment capacity.The paper proposes conceptual foundations for developing a regional strategy aimed at improving service quality, which involves the integration of strategic management tools, place marketing instruments, service standardization, and human capital development. Particular attention is paid to mechanisms of coordination between local authorities, business entities, and educational institutions in order to create a comprehensive regional service quality management system.The implementation of the proposed strategic approaches will contribute to increasing customer satisfaction, strengthening the tourist attractiveness of Zakarpattia, and ensuring the sustainable development of the hotel and restaurant sector in the long term.
Keywords: project management office; risk management; project management; sustainability; development; unstable environment; efficiency